POLITIK BERJENIS KELAMIN LAKI-LAKI? (KETERWAKILAN PEREMPUAN DI DPRD PROVINSI SULAWESI TENGGARA PADA PEMILU 2014) - Asliah Zainal (Institut Agama Islam Negeri Kendari, 2015)
AbstractWomen representation in politics in fact still has not showed in maximum results, both at the national and local level. This study was conducted to examine the dynamics of women representation Southeast Sulawesi Provincial Parliament at the general election in 2014. This studi used a sample of four political parties, PAN as the category of the ruling party and the first winner, the Golkar Party as the old political party and the second winner, Gerindra as a new political party with the acquisition of a significant voice as the fifth winner, and the PPP as an old and Islamic political party. This study shows that the women representation in Southeast Sulawesi Provincial Parliament has eight chair or 18 % within 45 of total legislators. This number is a slight increase compare to the general election in 2009 with only reached seven chair or 16% of women legislators. Among eight women legislators, six women or 75% were come and influenced by the power. Key Words: women and politic, affirmative action, patriarchy. AbstrakWacana keterwakilan perempuan dalam bidang politik masih belum menunjukan hasil yang maksimal, baik pada level nasional maupun lokal. Studi ini dilakukan untuk mengkaji dinamika keterwakilan perempuan di DPRD Provinsi Sulawesi Tenggara pada Pemilu 2014. Penelitian ini menggunakan sampel empat partai politik peserta Pemilu 2014, yaitu PAN sebagai partai penguasa dan pemenang pertama, Partai Golkar sebagai partai lama dan pemenang kedua, Partai Gerindra sebagai partai baru dengan suara yang cukup signifikan, dan PPP sebagai partai lama dengan basis Islam.Studi ini menunjukan bahwa Keterwakilan perempuan di DPRD Provinsi Sulawesi Tenggara pada Pemilu 2014 mendudukan 8 orang legislator perempuan dari 45 legislator (18%), sedikit meningkat dari pemilu 2009 yang hanya mencapai 7 orang legislator perempuan 16%). Dari delapan orang legislator perempuan, 6 orang atau 75% lahir dari rahim kekuasaan.Kata Kunci: perempuan dan politik, affirmative action, patriarki